Penerapan Manajemen Sumber Daya Manusia dalam Meningkatkan Kompetensi Pekerja di Era Digital pada Kelompok UMKM Pemula KEDU EMAS di Kecamatan Kelapa Dua Kabupaten Tangerang Provinsi Banten - Harapan, Augus Hasanudin; Tantri, Tantri; Gaotama, Tito Arrya; Fahri, Adam Miftahul; Ananda, Reza Kiki; Mukrodi, Mukrodi; Wahyudi, Wahyudi (Jurnal PKM Manajemen Bisnis, 2024)
This community service activity is entitled “Application of Human Resource Management in Improving Worker Competencies in the Digital Age at the KEDU EMAS Starter MSME Group in Kelapa Dua District, Tangerang Regency, Banten Province”. This activity was carried out on Sunday, July 14, 2024 and was attended by 22 students and 6 Pamulang University assistant lecturers. The general objective of this community service activity is the application of human resource management knowledge to improve competencies in the current digital era in KEDU EMAS MSMEs, Kelapa Dua District. The methods applied include surveys, direct material delivery, as well as consultation and discussion regarding the application and management of human resources. This community service activity succeeded in providing an understanding to KEDU EMAS MSME players regarding the management, training and development of human resources in an effort to develop community businesses in Kelapa Dua District.